Lepidagathis sabui (Acanthaceae), a new species from the lateritic plateaus of Konkan region of Maharashtra, India - Chandore, Arun Nivrutti; Borude, Devidas Bhausaheb; Madhav, Nilesh Appaso; Yadav, Shrirang Ramachandra (Phytotaxa, 2020)
Lepidagathis sabui, a new species of Acanthaceae is described and illustrated from the Konkan region of Maharashtra, India. It is closely related to L. prostrata, but differs by linear, spinulose, glabrous leaves, axillary spikes, recurved bracts and 5–7-nerved outer sepals. Coloured photographs and illustrations of new species and key to the Indian species having spinescent bracts, 5-partite calyx and 2-seeded capsule are provided to facilitate the identification.